Preparing students for the future through developing evaluative judgement. (5th October 2020) - Naidoo, Ornissa; Tai, Joanna; Penman, Merrolee
Abstract: In today's environment, health students need to be prepared for an ever changing workplace and workforce. They need to understand what demonstrates good quality work and how to assess their standard of work. Evaluative judgement can contribute to student and graduate self‐regulation and autonomy in their learning. This toolbox article describes how to implement strategies for developing evaluative judgement in allied health placements. These strategies were developed as part of an occupational therapy program in rural Western Australia, where experiential education is provided through service‐learning with both direct and indirect supervision. Practical advice is provided on the use of peer‐assisted learning, rubrics, self‐assessment and feedback. Challenges and opportunities in implementing strategies to develop evaluative judgement, such as how to achieve effective feedback, are also discussed. The suggested toolbox may be adapted to various clinical placement contexts. Developing evaluative judgement can help to prepare our students to be lifelong learners. This article empowers educators to promote this capability in their students to create work ready graduates, who are able to operate independently and in rapidly evolving, technologically enabled environments